1995
DOI: 10.1111/j.1600-051x.1995.tb01773.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effects of an Nd:YAG laser on subgingival calculus, dentine and cementum

Abstract: The aim of this study was to evaluate the effects of Nd:YAG laser treatment on subgingival calculus, cementum and dentine, in vitro at different power settings and durations. The study included 2 experiments. In the 1st experiment, 32 extracted teeth with calculus were divided into 8 laser treatment groups. Each tooth was treated on 2, 3 or 4 sites. In the 2nd experiment. 3 extracted cementum covered teeth and 3 extracted root planed teeth with exposed dentine were selected. 1 surface of each tooth was subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 6 publications
0
22
2
3
Order By: Relevance
“…The American Academy of Periodontology, in its position statement on lasers in ENAP, 15 states 'The Academy is not aware of any published data that indicates that the ENAP laser procedure is any more effective for these purposes than traditional scaling and planing'. 12,[16][17][18][19][20][21][22] This is sharply contrasted by reports by Gregg and McCarthy, reported in later journals. [23][24][25] In 2004 in a study presented by Evans 26 to review the new attachment procedure on a sample of six cases, evidence was given to show new cementum and bone growth, including periodontal ligament.…”
Section: De-epithelialisation Of the Periodontal Pocketcontrasting
confidence: 55%
“…The American Academy of Periodontology, in its position statement on lasers in ENAP, 15 states 'The Academy is not aware of any published data that indicates that the ENAP laser procedure is any more effective for these purposes than traditional scaling and planing'. 12,[16][17][18][19][20][21][22] This is sharply contrasted by reports by Gregg and McCarthy, reported in later journals. [23][24][25] In 2004 in a study presented by Evans 26 to review the new attachment procedure on a sample of six cases, evidence was given to show new cementum and bone growth, including periodontal ligament.…”
Section: De-epithelialisation Of the Periodontal Pocketcontrasting
confidence: 55%
“…However, the laser ablates the hard tissues as it removes calculus, which has hindered its use in this capacity. Studies have also shown that calculus removal by Nd:YAG laser is insufficient as compared to that achieved by hand instrumentation (Radvar et al, 1995). The Er:YAG laser has undergone extensive study since its introduction by Zharikov in 1974 (Tseng and Liew, 1990).…”
Section: Laser-based Technologymentioning
confidence: 98%
“…Laser applications in the field of periodontology have been of enormous scientific interest throughout the last decade and a variety of laser systems have been investigated in numerous in vitro [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and in vivo studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. In the treatment of inflammatory periodontal diseases, lasers may contribute to the bacterial reduction in periodontal pockets as well as to the removal of calculus and granulation tissue and can be used for contouring hyperplastic gingiva.…”
Section: Introductionmentioning
confidence: 99%